Exploring the optimal reverse supply chain for e-waste treatment under Chinese government subsidy. (1st January 2022) - Wang, Juntao; Li, Wenhua; Mishima, Nozomu; Adachi, Tsuyoshi
Highlights: This study models different formal channel structures under government subsidy. The study considers both price insensitive/sensitive overall collection quantity. It concludes the positive influence of the subsidy on the formal channel. Deriving optimal subsidies from the aspect of minimizing informal channel's profit. Exploring optimal formal channel structures for formal recyclers and the government. Abstract: This study aims to analyze the influence of Chinese government subsidy on e-waste treatment formal and informal reverse supply chains (RSC) and to explore the optimal formal channel structure. Under the formal recycler-Stackelberg game, we establish three game theory models respectively under the conditions of price insensitive and price sensitive overall collection quantity. In each model, a dual-channel RSC, the green technology investment decision of formal recycler and a subsidy for formal recycler are modelled. Besides, the three models are different in collectors and collection effort implementers of the formal channel. Through mathematical modelling and comparison analysis, the study concludes that the best choice for the formal recycling enterprises is to establish its own collection channel or centralize other independent collection channels. Under the condition of price insensitive overall collection quantity, the suboptimal choice is to implement collection effort positively. Under the condition of price sensitive overall collection quantity, the suboptimal choice is to outsource the collection effort when formal recycling enterprises benefit more from the collection effort. And the phenomenon is more outstanding when the overall collection quantity can be greatly improved by the collection price. For governments, they are recommended to prudently implement the subsidy and determine the amount of subsidy because the subsidy may benefit informal channels and the effectiveness of the subsidy varies along with formal channel structures. This study is beneficial for the promotion of formal RSC by providing the optimal channel structure for formal recycling enterprises and indicating the optimal subsidy for governments.